Sacred Spaces of the Mari Culture. Signs and Typologization of the Mythologized Landscape - German Yu. Ustyantsev; Diana Yu. Efremova; Tamara L. Serebrennikova (Финно-угорский мир)
Introduction. Amid growing interest from the public and researchers in the pre-Christian, nature-centered beliefs of the peoples of the Volga region, issues related to the perception of natural landscapes and their use in ritual practices have gained renewed relevance. The study aims to propose key factors for the qualitative description of the sacred landscape of contemporary Mari communities: the degree of development, the orderliness of the locus, its mythological image, and its role in ritual practices. Based on these factors, the authors present their own typology of sacred toposes within Mari culture.